2018
DOI: 10.1021/acs.inorgchem.8b01979
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Binding to Dirhodium(II) Tetraacetate

Abstract: The reaction between antitumor active dirhodium(II) tetraacetate and DL-methionine (HMet) was followed in aqueous solution and showed initially mixtures of 1:1 and 1:2 adducts [Rh2(AcO)4(HMet)(H2O)] (AcO− = CH3COO−) and [Rh2(AcO)4(HMet)2] formed at room temperature (RT), as evidenced by UV-vis spectroscopy and electrospray ionization mass spectrometry (ESI-MS). Rh K-edge extended X-ray absorption fine structure (EXAFS) spectroscopy confirmed methionine thioether binding to the axial positions of the Rh2(AcO)4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…In this structure, the Rh(III) distance is 3.18 ± 0.02 Å. This distance is similar to that previously found for the aerobic reaction product from aqueous solutions of Rh 2 (O 2 CCH 3 ) 4 and glutathione and in agreement with EXAFS data [ 22 , 49 ]. Thus, it seems that in our structure the acetate and the carboxylate C-terminal tails of the two symmetry-related molecules can bridge two metal centers acting as the sulfur atoms in the Rh(III)–S–Rh(III) unit found in the product of the reaction with sodium thiolate [ 49 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In this structure, the Rh(III) distance is 3.18 ± 0.02 Å. This distance is similar to that previously found for the aerobic reaction product from aqueous solutions of Rh 2 (O 2 CCH 3 ) 4 and glutathione and in agreement with EXAFS data [ 22 , 49 ]. Thus, it seems that in our structure the acetate and the carboxylate C-terminal tails of the two symmetry-related molecules can bridge two metal centers acting as the sulfur atoms in the Rh(III)–S–Rh(III) unit found in the product of the reaction with sodium thiolate [ 49 ].…”
Section: Resultssupporting
confidence: 89%
“…In solution studies demonstrated that dirhodium carboxylate compounds are able to bind proteins [ 12 , 22 , 23 , 26 , 28 , 29 ]. However, there are only very scarce structural information on this interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, [ImH]- trans -[RhCl 4 ( 3 N-imidazole) 2 ], the Rh­(III)–imidazole analogue of KP1019, and [Na·2DMSO]- trans -[RhCl 4 ( S -dmso)­( 3 N -imidazole)], the Rh­(III) analogue of NAMI-A, were inactive both in vitro and in vivo. , Rh has stable oxidation states and coordination geometries of Rh­(III) (octahedral), Rh­(II) (dimeric lantern), Rh­(I) (square planar), respectively. , A number of bioactive complexes of each oxidation state have been evaluated in recent years (e.g., Rh­(I) N-heterocyclic carbenes, photoactive Rh­(II)–polypyridyl complexes, , and organometallic Rh­(III)–Cp* agents (Cp* = pentamethylcyclopentadienyl ligand) ). Notably, dirhodium­(II) tetraacetate, [Rh 2 (OAc) 4 ], readily reacted with methionine and cysteine under ambient conditions (aqueous solutions, pH 7.4, room temperature, and aerobic conditions) and generated various monomeric Rh­(III) species. The Ru anticancer complexes have oxidation states of either Ru­(III) (e.g., NAMI-A and KP1019) or Ru­(II) (organometallic Ru­(II)–arene complexes , ). Reduction of Ru­(III) to Ru­(II) has been proposed to be the key mechanism of action for the anticancer activities of Ru­(III) complexes, but the latest biological speciation using X-ray absorption spectroscopy (XAS) argued strongly against this hypothesis. , Although detailed mechanistic studies on these Rh­(III) complexes were not pursued, these observations suggested alternative mechanisms of action for the anticancer activities of the Rh­(III) complexes in comparison to the much studied Ru and Pt anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The dirhodium tetraacetate complex [Rh 2 (μ-O 2 CCH 3 ) 4 ] includes a Rh­(II)–Rh­(II) bond with four carboxylates playing the role of bridging ligands arranged in a lantern-like form around the central bimetal unit, whereas neutral solvent molecules (L) occupy the axial coordination sites. Although causing toxic side effects, this complex has a proven activity against several cancer types, such as sarcoma 180, P388 leukemia, L1210 tumors, and Ehrlich-Lettre ascites carcinoma. Nevertheless, its mode of action is not yet disentangled despite several studies on its interaction with various proteins, although it is hypothesized that its biomolecular targets are single- and double-stranded DNA, proteins, peptides, , and amino acids. Moreover, interaction of dirhodium compounds with peptides and proteins was investigated in the framework of protein modification with the aim of designing artificial metalloenzymes. , Usually, Rh-based complexes are coordinated to proteins either via the covalent linkage, involving direct binding of these metal complexes to proteins, , or via the dative anchoring which is based on the formation of noncovalent interactions between protein atoms and Rh ligands as well as coordinative bonds between protein side chains and Rh centers . There are experimental pieces of evidence of the Rh-complex selectivity toward side chains of Asn, Asp, His, Lys, and the C-terminal carboxylate. ,, …”
Section: Introductionmentioning
confidence: 99%